The Effect of Internal Control System, Financial Pressure, and Organizational Culture on the Tendency of Financial Statement Fraud - Ni Kadek Dwi Anggreni; I Gde Ary Wirajaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Fraud is an unlawful act characterized by intentional misconduct, malicious intent, manipulation, concealment, and abuse of trust, deliberately committed by individuals or groups to gain personal benefits. Financial statement fraud can result from various factors such as weak internal control systems, financial pressures, and organizational culture. This study focuses on understanding the factors influencing the occurrence of financial statement fraud in rural banks (BPR) in Denpasar City. A total of 204 respondents from 22 BPRs were selected using purposive sampling. The study reveals that internal control systems do not have a significant effect on the tendency to commit financial statement fraud. However, financial pressure was found to have a positive and significant impact on the likelihood of financial statement fraud, suggesting that employees or management under financial strain may resort to fraudulent activities. On the other hand, organizational culture, characterized by ethical practices and strong values, showed a negative and significant effect, indicating that a strong ethical culture helps reduce fraudulent behavior in BPR